Effect of acute sodium bicarbonate intake on sprint-intermittent performance and blood biochemical responses in well-trained sprinters - AbuMohd, M. F.; Alsababha, W.; Haddad, Y.; Obeidat, G.; Telfah, Y. (Montenegrin Journal of Sports Science and Medicine, 2021)
The present study was designed to determine the acute effect of sodium bicarbonate (NaHCO3) on the number of sprint repetitions during sprint high-intensity intermittent testing. In addition, blood biochemical (pH, HCO3-, and lactate) responses measured in three occasions were investigated. Thirteen male welltrained sprinters (24.65±3.44 yrs) performed two consecutive trials (7 days apart). Athletes were assigned randomly either to ingest a single dose of NaHCO3 (0.3 g/kg) 1 h prior to exercise or placebo using a double-blind crossover design. The intermittent sprint test consisted of 60 s treadmill sprints (90% of maximal work done) and 30-s recovery repeated intermittently until volitional exhaustion. Blood samples were collected from all athletes before exercise, after 1 h of dose intake, and after exercise in each trial. Paired sample t-testing showed that athletes complete significantly more sprint repetitions (p=0.036) during the intermittent sprint test with NaHCO3 (6.846±3.114) than with the placebo (5.538±3.872). Data also revealed no differences between trials in all blood responses at pre-exercise. Af-ter 1 h of dose consumption, however, blood pH and HCO3- were higher with NaHCO3 than with placebo (p<0.05), but no differences were noted in lactate between trials (p>0.05). After completion of the test, all blood responses were significantly higher with NaHCO3 than with placebo (p<0.05). In conclusion, intake of 0.3 g/kg of NaHCO3 1 h prior to treadmill sprint-intermittent performance increased sprint repetitions in welltrained sprinters, probably due to activated glycolysis caused by intracellular protons efflux into the blood